Pedagogical Content Knowledge of nursing freshman professors in medium-level technical education - Souza,Daniela Maysa de (2020)
ABSTRACT Objectives: to analyze the practice and construction processes of Pedagogical Content Knowledge of freshman professors, in secondary education in nursing. Methods: a collective case study with a qualitative approach. Data collection with biographical interview, non-participant observation of sessions and group interview. With the results interpreted in the light of Shulman's theoretical framework, content analysis enabled the creation of the category Manifestation of Pedagogical Content Knowledge. Results: predominance of traditional teaching practices, with an attempt at more flexible postures, with pedagogical knowledge and encouragement for student reflection. Final Considerations: the transition from the traditional model to a dialogical teaching (with the student's role) highlights the process of expanding Pedagogical Content Knowledge of, such as learning in and about the practice itself, seeking to strengthen teaching knowledge. A manifestation of reflective thinking was evidenced, with a perception of teaching professionalization.